Acceptance lowers stress reactivity: Dismantling mindfulness training in a randomized controlled trial. (January 2018) - Lindsay, Emily K.; Young, Shinzen; Smyth, Joshua M.; Brown, Kirk Warren; Creswell, J. David
Highlights: Mindfulness interventions train one to monitor present experiences with acceptance. Acceptance is posited as a key mechanism for mindfulness stress reduction effects. Monitoring and acceptance instructions were dismantled in brief remote trainings. Monitor + Accept reduced biological stress reactivity vs Monitor Only and control Tx. Acceptance is a critical mindfulness training component for reducing stress biology. Abstract: Objective: Mindfulness interventions, which train practitioners to monitor their present-moment experience with a lens of acceptance, are known to buffer stress reactivity. Little is known about the active mechanisms driving these effects. We theorize that acceptance is a critical emotion regulation mechanism underlying mindfulness stress reduction effects. Method: In this three-arm parallel trial, mindfulness components were dismantled into three structurally equivalent 15-lesson smartphone-based interventions: (1) training in both monitoring and acceptance (Monitor + Accept), (2) training in monitoring only (Monitor Only), or (3) active control training (Coping control). 153 stressed adults (mean age = 32 years; 67% female; 53% white, 21.5% black, 21.5% Asian, 4% other race) were randomly assigned to complete one of three interventions. After the intervention, cortisol, blood pressure, and subjective stress reactivity were assessed using a modified Trier Social Stress Test. Results: As predicted, Monitor + Accept training reduced cortisol and systolic blood pressure reactivity compared to Monitor Only and control trainings. Participants in all three conditions reported moderate levels of subjective stress. Conclusions: This study provides the first experimental evidence that brief smartphone mindfulness training can impact stress biology, and that acceptance training drives these effects. We discuss implications for basic and applied research in contemplative science, emotion regulation, stress and coping, health, and clinical interventions.